Light or temperature; that is the question. The circadian rhythm of the silvery mole-rat (Heliophobius argenteocinereus) - Rýpalová, Kateřina (Jihočeská univerzita, 2016)
Subterranean rodents are interesting model group for studying of the circadian timing system due to their cryptic lifestyle and challenging living conditions. The filed data indicate that the locomotor activity of the silvery mole-rat (Heliophobius argenteocinereus) is influenced by temperature cycle, but the confirmation in laboratory study was to date missing.
Light or temperature; that is the question. The circadian rhythm of the silvery mole-rat (Heliophobius argenteocinereus)
Keywords: Circadian rhythm; circadian activity; silvery mole-rat; light; temperature; Circadian rhythm; circadian activity; silvery mole-rat; light; temperature